Keabsahan Surat Keputusan Pemberian Hak Atas Tanah Tanpa Disertai Surat Setoran Pajak - Tornado, David Mars; Riza, Marwati; Nur, Sri Susyanti (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2021)
The granting of land rights is one way for legal subjects to be able to obtain a right to land in Indonesia. This study aims to determine the legal implications of the Decree on Granting Land Rights issued by the National Land Agency without implementing Article 7 of the Republic of Indonesia Government Regulation Number 34 of 2016 concerning Income Tax. This research is empirical legal research. The results of the research show that the Decree on the Granting of Rights to Land is still valid without implying that it is null and void, while Article 7 of the Republic of Indonesia Government Regulation Number 34 of 2016 is not in line with the principles in the theory of legal certainty and is not effective in its application or enforcement.